MCC950 Ameliorates Acute Liver Injury Through Modulating Macrophage Polarization and Myeloid-Derived Suppressor Cells Function - Yan, Wei; Shen, Yingchun; Huang, Jinny; Lu, Ling; Zhang, Qian (Frontiers in Medicine, 2021)
Acute liver injury (ALI) raises high mortality rates due to a rapid pathological process. MCC950, a highly selective NLRP3 inhibitor, has already been reported to show strong hepatoprotective effects in many different liver diseases. In this study, we unveiled the role of MCC950 in carbon tetrachloride (CCl4) induced ALI and its underlying molecular mechanisms on day 1, 2 and 3. MCC950 could significantly inhibit liver injury, evidenced by decreased serum ALT and AST levels on day 1 and 2, increased ALB level on day 3 and decreased histological score during the whole period. Moreover, lower M1 macrophage related to pro-inflammatory genes expression was observed in MCC950 treated ALI mice on day 1, while MCC950 pretreatment also polarized macrophage to M2 phenotype indicating anti-inflammatory response on day 2 and 3. Additionally, MDSC was significantly increased in blood, liver and spleen in ALI mice at different time course. Specifically, upregulated MDSC proportions were found in blood and spleen on day 1 and 2, but showed decreased trend on day 3. However, liver MDSC numbers were increased on day 2 and 3 but no significance on day 1. In conclusion, MCC950 pretreatment alleviates CCl4-induced ALI through enhanced M2 macrophage and MDSC function at different time points of ALI. Further understanding of MCC950 in ALI may be a new potential therapeutic strategy.